THE MANIFESTATION OF THE EPIDEMIC PROCESS OF VIRAL HEPATITIS A IN THE TERRITORIES OF JIZZAKH REGION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
According to the 2024 Global Hepatitis Report of the World Health Organization, the number of victims of this disease continues to grow. Hepatitis ranks second in the world among infectious diseases by mortality, and 1.3 million people die from this disease annually, which is equivalent to deaths caused by tuberculosis. In our country and many other nations, the morbidity (incidence) rate of viral hepatitis A has remained high to date. In Uzbekistan, the incidence of viral hepatitis A remains elevated today – its rate per 100,000 population in 2010 exceeded 100, however, compared to the 1990s, the incidence rate decreased by 3.7 times [59,64,70]. Currently, in order to improve the prevention of all viral hepatitis infections in our republic, measures are being implemented based on the Order of the Ministry of Health of the Republic of Uzbekistan dated August 27, 2018, № 542 “On further improving measures for diagnosis, treatment, and prevention of viral hepatitis in the Republic of Uzbekistan.” Although in recent years viral hepatitis A (VHA) shows a tendency of decline, epidemic outbreaks are periodically registered in certain regions. Due to changes in the clinical course and epidemiological characteristics of VHA at the present stage, it is necessary to study these epidemiological features. In Jizzakh region, such scientific research has been carried out insufficiently. Therefore, at present, it is necessary to conduct studies to evaluate the effectiveness of vaccination-preventive measures, improve prevention of viral hepatitis A, and enhance epidemiological control.